Layla - Hoover, Colleen (Seattle : Montlake, Amazon Pub., 2020)
"When Leeds meets Layla, he$1 (Bs convinced he$1 (Bll spend the rest of his life with her$1 (Buntil an unexpected attack leaves Layla fighting for her life. After weeks in the hospital, Layla recovers physically, but the emotional and mental scarring has altered the woman Leeds fell in love with. In order to put their relationship back on track, Leeds whisks Layla away to the bed-and-breakfast where they first met. Once they arrive, Layla$1 (Bs behavior takes a bizarre turn. And that$1 (Bs just one of many inexplicable occurrence."--s
Keywords: Man-woman relationships -- Fiction; Assault and battery -- Fiction; Triangles (Interpersonal relations) -- Fiction; Romance fiction; Paranormal fiction